(untitled) (Journal of Universal Science Research, 2024)
Metabolic disorders, including diabetes and cardiovascular diseases (CVDs), are increasingly prevalent among the young population in Uzbekistan. This article explores the importance of self-control and adopting a healthy lifestyle in preventing these disorders. It discusses the current situation in Uzbekistan, highlighting the need for early intervention strategies. The article emphasizes the role of education and awareness in promoting healthy behaviors and suggests practical steps for individuals to take control of their health. By focusing on prevention through lifestyle changes, Uzbekistan can reduce the burden of metabolic disorders and improve the well-being of its young population.